The impact of operative correction of equinus in cerebral palsy on gait patterns - Horsch, Axel; Petzinger, Lara; Deisenhofer, Julian; Ghandour, Maher; Klotz, Matthias C. M.; Renkawitz, Tobias; Putz, Cornelia (Foot & ankle international, 2024)
Background: This study aimed to evaluate gait outcomes and strength following the surgical correction of equinus in cerebral palsy (CP) based on different surgical procedures. We included the Baumann and Strayer procedures, as well as the Achilles tendon lengthening (ATL). - Methods: A retrospective analysis was performed in patients with infantile, bilateral CP who received instrumental 3D gait analysis before and after surgical correction (18.66 months postoperatively). Patients were divided into 3 groups: Strayer surgery, Baumann surgery, and ATL. Gait performance and muscle strengths were compared between studied surgeries. - Results: A total population of 204 patients (15.43 years) with 341 operated lower limbs (LLs) was analyzed. Dorsiflexion in swing and stance phases significantly improved in all groups postoperatively. The Strayer and the ATL group showed higher postoperative dorsiflexion than the Baumann group. However, no loss of strength was observed with the Baumann method. Maximum power improved in this group postoperatively. An 8.2% loss in calf muscle strength was recorded in the Strayer group. - Conclusion: Operative pes equinus treatment successfully improved the gait of children and adults with CP postoperatively. There were differences in postoperative results between studied operative techniques regarding range of motion and power. - Level of Evidence: Level III, retrospective cohort study.